Healthy Nurses: Tips for Enhancing Mental, Emotional, and Spiritual Well-being - Monica Jaramillo (OPI Napoli, 2023)
Introduction: Recent literature suggests a detrimental burden affecting nurses of all settings and backgrounds. Mental and emotional problems such as moral distress, burnout, compassion fatigue, depression, and severe stress are a few of the many issues nurses are experiencing worldwide. Nurses need enhanced guidance and support regarding caring for their health and well-being. Discussion: It is imperative to advocate for healthier nurses worldwide. Nurses are experiencing several mental issues and burnout due to a lack of resilience and self-care management. All key stakeholders internationally need to aid nurses with feasible tools that promote mindfulness and improvement of self-care while ensuring stability. The key to enhancing nurses' mental, emotional, and spiritual well-being could be to offer holistic support conducive to mind-body-spirit and physical health.